Special Issue on Structural and Thermo-Mechanical Analyses in Nuclear Fusion Reactors - Pietro Arena; Pietro Alessandro Di Maio (Applied Sciences, 2022)
Nuclear fusion is one of the most promising technologies to be adopted for the production of electricity [...]